FAMILIES' PERCEPTIONS REGARDING THE ORGANIZATION OF PRIMARY HEALTH CARE FOR THEIR CHILDREN - Ana Paula Pereira Fernandes; Ana Maria Cosvoski Alexandre; Ana Paula Dezoti; Verônica de Azevedo Mazza (Universidade Federal do Paraná, 2014)
This descriptive, qualitative research aimed to understand, based on the families' perception, the organization and the practices of care for the child in primary health care; the study was undertaken with 45 representatives of families of children aged from zero to five years old, enrolled in the programs of three health centers in a municipality in the metropolitan region of Curitiba, in the state of Paraná. The data was collected between September 2008 and February 2009, through three focus groups, and was analyzed using categorical thematic analysis. Three empirical categories emerged: Access to the health services; Integrality; and Embracement. In the perception of the families, there are issues which are favorable in relation to the reformulation of the practices of the programs for child health. However, they mention barriers to access, resulting from issues of organization of the services for the population not included in these programs. It is therefore considered essential for the families to participate in the planning of the health care actions for the child.